Respiratory health problems among ferroalloys factory workers - Shimaa A. Elghazally; Hussein H. Zayet; Ayah A. Alkarn; Alaa Bazeed; Mariam Roshdy ElKhayat (The Egyptian Journal of Bronchology)
Abstract Background Ferrosilicon alloys are a mixture of iron and silicon. It offers better iron characteristics such as hardness, strength, and resistance to corrosion and heat by adding alloys of ferrosilicon to steel and cast iron. The ferrosilicon alloy industry workers are exposed to many hazards that can affect their respiratory function due to exposure to silica dust which is present in all steps in this industry mainly from furnaces, in addition to exposure to irritant gases in refining and casting operations. Thus, the current study was conducted to estimate the respiratory problems prevalence especially silicosis among workers of ferroalloy factories. Results All studied workers (100%) were males with a mean (± SD) age of 50.15 ± 5.77 years. Seventy percent of workers had been working for ≥ 20 years and 76.4% were working in places with high levels of exposure. About one-third of the studied workers were diagnosed with silicosis. There was a statistically significant higher occurrence of silicosis among workers aged ≥ 50 years old. Work duration and level of exposure were significant predictors of silicosis occurrence among studied workers. Conclusion Ferroalloy factory work environment affects the respiratory health of the workers and impairs their pulmonary function. It may increase the risk of developing silicosis which impacts the effectiveness of their work and quality of life. Workers in ferroalloys factories must receive regular medical care, and safety precautions are recommended. Trial registration ClinicalTrials.gov. NCT05374148. Registered May 13, 2022.